WARRI CRISES: CAUSES AND IMPACT ON THE OIL INDUSTRY IN THE NIGER DELTA - AVI, Eduvwie Nyerohwo (EBSU Journal of Social Sciences and Humanities, 2021)
The destructive nature of the Warri crises and its impact on the socio-economic lives of the people of the State have being one too many, especially establishing a new form of attitude of the people towards organising themselves. This is seen from the issues surrounding the cause of the crises, particularly accumulation of arms and ammunition through proceeds of illegal bunkering and pipeline vandalism among communities living within the riverine and interior areas. Thus, the study argues that under-development, failure of OMPADEC to deliver on its mandate, and the mode of compensation of oil companies in these communities are central to the Warri crises, although they were termed underlying causes. For instance, the collapsed of the non-oil sector and, also, government inability to develop the area necessitated a feeling of neglect by the people thus causing disaffection and distrust among ethnic groups. The study observes that in the course of the 1997 crisis, the opposing groups engulfed in brawl and their members were targeted, while the other crises; 2001 and 2003, oil companies became subject of attacks from the Ijaw group who felt maginalised from oil activities in the area. The study concludes that militancy, youth restiveness, inter-communal and intra-communal violent conflicts in Delta State are tied to the various crises in Warri, as it became a norm for communities to amass weapons in protection against perceived threats from other communities. The study employs primary and secondary sources of data and adopts both qualitative and descriptive methods of historical research in its analysis.